Influence of inherent parameters within virtual systems on cognitive rehabilitation - Santamaría-Villacís, Marlon (2022)
The study is based on a theoretical review of the current literature in the field of virtual systems applied to cognitive rehabilitation, focusing on the influence of different parameters such as immersion, presence, cues, and distractors. To this end, it is proposed to design applications with adjustable features that allow different levels of inherent parameters to be evaluated. For experimental purposes, it is initially proposed to use the application with healthy patients and then continue with patients with a neurodegenerative disease.